LEVANTAMIENTO DE TEMPLOS CATÓLICOS EN CHILE. 1925-1960. CUATRO CASOS DE ESTUDIO - Gaete, Marcial Sánchez; Navasal, María José Castillo (Cordis: Revista Eletrônica de História Social da Cidade, 2021)
The Church is separated from the State of Chile, which will mark a new process since the arrival of the Spaniards to the national territory, so the institution will have to find the most appropriate method to support itself economically and also raise its new temples without direct contribution of the State. The State had not fulfilled its obligation to grant all the necessary and customary monetary contribution to maintain the Catholic Church. So the clergy began to pressure and demand from their parishioners the resources to support themselves, keeping a glance of what they had comfortably received, without assuming, in many cases and especially the curia, of the general needs that had also affected the population.